Integration of Innovative Photovoltaic Technology to the Railway Trains: A Case Study for Istanbul Airport-M1 Light Metro Line - Kilic, Beyhan; Dursun, Erkan (IEEE, 2017)
Urban metro system consumes huge amount of electrical energy. Therefore, energy consumption, operating costs, and environmental impact of metropolitan transportation should be kept under the control. Capacity expansion and operation costs of urban rail systems are brought forward energy efficiency improvements in the urban rail transportation. Accordingly, there is urgent need to use renewable energy sources and energy efficiency measures for railway systems. Photovoltaic (PV) technology has not been widely applied to railway vehicles. It can lead to considerable reductions in greenhouse gas emissions. In this paper, a feasibility study on the use of PV panels for the interior lighting of the urban rail vehicles was performed. The feasibility study was carried out with HOMER software, which is version 3.1.4. After performing a literature review about integrating renewable energy sources to railway systems, a case study is developed to explore the application of solar energy systems for internal lighting of vehicles having got mathematical models of the solar system. Different scenarios can be calculated with this simulation tool, helping the decision makers when selecting innovative solutions.
Keywords: railway engineering; solar energy; energy management; Computer Science; Engineering